Associations of sedentary behavior, sedentary bouts and breaks in sedentary time with cardiometabolic risk in children with a family history of obesity. - Travis John Saunders; Mark Stephen Tremblay; Marie-Ève Mathieu; Mélanie Henderson; Jennifer O'Loughlin; Angelo Tremblay; Jean-Philippe Chaput; QUALITY cohort research group (PLoS ONE, 2013)
Although reports in adults suggest that breaks in sedentary time are associated with reduced cardiometabolic risk, these findings have yet to be replicated in children.To investigate whether objectively measured sedentary behavior, sedentary bouts or breaks in sedentary time are independently associated with cardiometabolic risk in a cohort of Canadian children aged 8-11 years with a family history of obesity.Data from 286 boys and 236 girls living in Quebec, Canada, with at least one biological parent with obesity (QUALITY cohort) were collected from 2005-2008, and analyzed in 2013. Sedentary behavior, light and moderate-to-vigorous physical activity were measured over 7 days using accelerometry. Leisure time computer/video game use and TV viewing over the past 7 days were self-reported. Outcomes included waist circumference, body mass index Z-score, fasting insulin, fasting glucose, triglycerides, HDL-cholesterol, C-reactive protein and a continuous cardiometabolic risk score.After adjustment for confounders, breaks in sedentary time and the number of sedentary bouts lasting 1-4 minutes were associated with reduced cardiometabolic risk score and lower BMI Z-score in both sexes (all p<0.05). The number of sedentary bouts lasting 5-9 minutes was negatively associated with waist circumference in girls only, while the number of bouts lasting 10-14 minutes was positively associated with fasting glucose in girls, and with BMI Z-score in boys (all p<0.05). Leisure time computer/video game use was associated with increased cardiometabolic risk score and waist circumference in boys, while TV viewing was associated with increased cardiometabolic risk, waist circumference, and BMI Z-score in girls (all p<0.05).These results suggest that frequent interruptions in sedentary time are associated with a favourable cardiometabolic risk profile and highlight the deleterious relationship between screen time and cardiometabolic risk among children with a family history of obesity.